Torrefaction of microalgal biochar as potential coal fuel and application as bio-adsorbent. (1st June 2018) - Gan, Yong Yang; Ong, Hwai Chyuan; Show, Pau Loke; Ling, Tau Chuan; Chen, Wei-Hsin; Yu, Kai Ling; Abdullah, Rosazlin
Graphical abstract: Highlights: Torrefaction is a promising conversion method in upgrading microalgal biomass. Wet torrefaction is a recent technology to improve HHV of wet microalgal biomass. Torrefied microalgae shows an applicable approach in solid fuel application. Microalgal biochar has unique properties suitable for bio-adsorbent application. Abstract: Microalgal biomass is the third-generation promising feedstock for production of biofuel and other valuable goods. The raw microalgal biomass and residues have low calorific value, high moisture, and high H/C and O/C atomic ratio which not suitable to use as solid fuel and many engineering applications. Torrefaction is a promising technique to upgrade microalgal biomass closed to solid coal properties by increasing the calorific value of microalgal biochar. However, the overview of torrefaction process for microalgal biochar is lacking in the literature study. Thus, an overview of recent dry and wet torrefaction of microalgal biomass is presented in this review. Wet torrefaction is a new technology for microalgal biochar production because it has some advantages compare with other pre-treatment methods. Besides, this review aims to provide a comprehensive overview of recent research for fuel property of microalgal biochar after torrefaction process. Different torrefaction temperature, gases and holding time lead to various solid yield, energy yield and calorific value of biochar are comprehensively discussed. In addition, the used of microalgal biochar as bio-adsorbent to remove pollutants in wastewater are included as well. In short, this is a comprehensive summary of recent torrefaction technology for microalgal biochar as fuel.